2020
DOI: 10.1093/jtm/taaa216
|View full text |Cite
|
Sign up to set email alerts
|

Predicting morbidity in older travellers during a short-term stay in the tropics: the ELDEST study

Abstract: Background: Older persons may suffer more from travel-related health problems because of aging and underlying chronic disorders. Knowledge on who is more likely to have these health problems helps to tailor travel health advice more specifically. This study aimed to determine predictors of travel-related morbidity in older travelers by assessing their pre-travel characteristics and performance using physical and cognitive functioning tests. Methods: Multicenter prospective cohort study among old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…In a study of Wieten et al 26% of the travelers visiting the travel clinic for pre-travel advice had a medical condition (often cardiovascular); this was doubled in older travelers [39]. However, in a prospective cohort study we found that exacerbations of pre-existing illness as a health problem while being abroad was only rarely reported by older travelers to the tropics [30]. In addition, the post-travel health status of affected travelers was unknown since no (medical) follow up was done by the MAC after discharging from the hospital or after the repatriation.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In a study of Wieten et al 26% of the travelers visiting the travel clinic for pre-travel advice had a medical condition (often cardiovascular); this was doubled in older travelers [39]. However, in a prospective cohort study we found that exacerbations of pre-existing illness as a health problem while being abroad was only rarely reported by older travelers to the tropics [30]. In addition, the post-travel health status of affected travelers was unknown since no (medical) follow up was done by the MAC after discharging from the hospital or after the repatriation.…”
Section: Discussionmentioning
confidence: 68%
“…Individuals with known or high risk for mental illness can travel, but are strongly advised to discuss their travel plan with a mental health professional [27,28]. Rofaiel et al [29] reported that very few mental health patient organizations have pre-travel information available online, while travel can have both negative and positive effects on (mental) health [30]. It is estimated that 10-20% of all repatriations concerned Data are presented as N (%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, across Europe, the average age of PLWH is increasing [2]; there are multiple lines of evidence that comorbidities are highly prevalent in ageing PLWH, adding age-related risks to HIV-related vulnerabilities [1,17]. Within the subpopulation treated with cardiovascular and/or diabetic drugs, the rate of pre-travel consultation was not higher, which means that these patients may not be aware of their increased vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Although the COVID pandemic caused a significant decline in worldwide travel [ 2 , 3 , 4 ], the growth in international travel is spiking again. Over the years, the profile of the passengers has also changed and includes an increasing number of children and the elderly, those with chronic illnesses, and an increased rate of travel to exotic destinations, including low–middle-income countries (LMIC) [ 5 , 6 , 7 , 8 , 9 ]. Information about travel-related morbidity is important for health practitioners to diagnose disease in returning travelers and for consulting those seeking pre-travel advice.…”
Section: Introductionmentioning
confidence: 99%